Interplay between Histomonas meleagridis and Bacteria: Mutualistic or Predator–Prey?. Issue 3 (March 2020) - Bilic, Ivana; Hess, Michael
Abstract : Histomonas meleagridis is an extracellular protozoan parasite and the aetiological agent of histomonosis, an important poultry disease whose impact is greatly accentuated by inaccessibility of any treatment. A special feature of the parasite is its intricate interplay with bacteria in vitro and in vivo, the focus of this article.